The impact of fiscal incentives on electric vehicle adoption in Europe: a dynamic approach - Marchioro, Flora (2021)
Monetary incentives have been used worldwide to decrease high upfront costs of electric vehicles (EVs) and foster their adoption, but few empirical studies have analysed the effectiveness of such policies in Europe. The present thesis investigates the influence of consumer-side fiscal incentives on European EV adoption figures in 2010-2019 through a generalised method of moments (GMM) model. By exploiting the dynamic nature of the dependent variable, and controlling for socio-economic and attitudinal country-level data, I showed that the incentive design and the strength of network externalities in the country are critical determinants for the impact of monetary incentives.